Feeding Practices and Its Association with nutritional status among Infants of Working Mothers of a Bangladeshi Garments Factory - Hye, Md Abdul; Hassan, Md Nazmul; Rahman, Md Obaydur; Haque, Mohammad Rezaul; Mondal, Md Tariqul Islam; Islam, Md Nazrul; Ahmed, Khondaker Mobasher; Adnan, Mohammad Ahad (Northern International Medical College Journal, 2025)
Background: Breastfeeding is considered as one of the most important factors for growth and development of infants, which offers tremendous health benefits to both child and mother. Breastfeeding provides all the energy and nutrients that the infant needs for the first 6 months of life and it continues to provide up to half or more of a child’s nutritional needs during the second half of the first year and up to one third during the second year of life. Objective:This study determinesthe feeding practices and its association with nutritional status among the infants of working mothers in a selected garments factory of Bangladesh. Methods: This cross-sectional study on 267 working womenwith infants aged 0 to 12 months of Garments Factory in Narayangonj was carried out at the Department of Pediatrics, Institute of Child and Mother Health (ICMH), Matuail, Dhaka.After takinga written consent of the study subjects were enrolled in the study. A detail history was taken regarding breastfeeding practices and complementary feeding as well as co-morbidities. Then anthropometry of infants was measured and plotted in CDC growth chart. Nutritional status was determinedby using Z-scores for weight-for-age (WAZ), weight-for-length (WLZ), length-for-age (LAZ). Z-scores of <-2 to -3 Z-score was considered moderately malnourished, while scores <-3 as severely malnourished. Results: The majority (58.8%) infants belonged to age 6-12 months. The mean age was found 6.70±2.77 months. More than half (52.4%) infants were male. Out of 267 mothers, 174(65.2%) respondents mentioned about initiation of breastfeeding within 1 to 12 hours, 200(74.9%) respondents had practice of colostrums feeding, 64(24.0%) given pre-lacteal feeding, and exclusive breastfeeding 58(21.72%). Mean duration of exclusive breast feeding was 2.9±0.8 months and 92(58.6%) mothers started complementary feeding by 6 months. Thirty two (50.0%) were given pre-lacteal feeds by honey. Majority 31.58% infants were given rice powder (suji) along with breastfeeding.In under 1 year of age, 23(8.6%) infants were found to have severe wasting, 42(15.7%) had severe stunting, 39(14.6%) had severe underweight, 13(8.3%) had severe malnutrition, 5(4.5%) had visible wasting and 9(3.4%) had bipedal edema. Moderate and severe wasting (WLZ), stunting (LAZ) and underweight (WAZ) were statistically significant (p<0.05) when compared with exclusive breastfeeding and non-exclusive breastfeeding infants respectively was well as appropriate complementary feeding and inappropriate complementary feeding. Conclusion: This study showed evidence of inappropriate feeding among working mothers. Due to inappropriate complementary feeding and non-exclusive breastfeeding, several forms of malnutrition (wasting, stunting, and underweight) predominated in their infants. Northern International Medical College Journal Vol. 14 No. 1-2 July 2022-January 2023, Page 609-615